Nature-Inspired Upward Hanging Evaporator with Photothermal 3D Spacer Fabric for Zero-Liquid-Discharge Desalination - Peng, Ye; Shao, Yang; Zheng, Longqing; Li, Haoxuan; Zhu, Meifang; Chen, Zhigang (Nano-Micro Letters, 2025)
While desalination is a key solution for global freshwater scarcity, its implementation faces environmental challenges due to concentrated brine byproducts mainly disposed of via coastal discharge systems. Solar interfacial evaporation offers sustainable management potential, yet inevitable salt nucleation at evaporation interfaces degrades photothermal conversion and operational stability via light scattering and pathway blockage. Inspired by the mangrove leaf, we propose a photothermal 3D polydopamine and polypyrrole polymerized spacer fabric (PPSF)-based upward hanging model evaporation configuration with a reverse water feeding mechanism. This design enables zero-liquid-discharge (ZLD) desalination through phase-separation crystallization. The interconnected porous architecture and the rough surface of the PPSF enable superior water transport, achieving excellent solar-absorbing efficiency of 97.8%. By adjusting the tilt angle (θ), the evaporator separates the evaporation and salt crystallization zones via controlled capillary-driven brine transport, minimizing heat dissipation from brine discharge. At an optimal tilt angle of 52°, the evaporator reaches an evaporation rate of 2.81 kg m−2 h−1 with minimal heat loss (0.366 W) under 1-sun illumination while treating a 7 wt% waste brine solution. Furthermore, it sustains an evaporation rate of 2.71 kg m−2 h−1 over 72 h while ensuring efficient salt recovery. These results highlight a scalable, energy-efficient approach for sustainable ZLD desalination. Highlights: 1 Successful fabrication of photothermal 3D polypyrrole polymerized spacer fabric with excellent water transport capability and high solar absorption efficiency. 2 The upward hanging model evaporator with reverse water feeding achieves an optimized solar evaporation rate of 2.81 kg m−2 h−1 with minimal heat (0.366 W) loss at a 52° tilt. 3 A mangrove leaf-inspired upward hanging model evaporator design separates evaporation and crystallization zones for zero-liquid-discharge desalination.